2012
DOI: 10.24035/ijit.02.2012.007
|View full text |Cite
|
Sign up to set email alerts
|

Dialogue of Life and Its Significance in Inter-Religious Relation in Malaysia

Abstract: Dialogue of life is a form of inter-religious dialogue which commonly takes place at any place and any time. It is a dialogical relation to promote amicable relation with people from different religions. It begins when one encounters, lives and interacts with the others and participates in daily life activities together. It is a social interaction which shows the involvement of non-elite participants in the inter-religious dialogue at the grass roots level. The nonelite participation in the inter-religious dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…While religion may not be the actual subject of concern in the discourses, the people draw from the values of their individual beliefs and traditions; and should the discussion about their relationship with God take place, it is because the people are basically religious and matters of religious interest form part and parcel of their daily discussion. (Sintang et al, 2012) Contributing to discourse on the dialogue of life within the context of its meaning and nature, (Kuruvachira, 2003) stressed that the dialogue of life is the first form of dialogue. He further stressed that it implies concern, respect and hospitality towards the other.…”
Section: Beyond Religious Fanaticism In Nigeria: Perspectives From Th...mentioning
confidence: 99%
“…While religion may not be the actual subject of concern in the discourses, the people draw from the values of their individual beliefs and traditions; and should the discussion about their relationship with God take place, it is because the people are basically religious and matters of religious interest form part and parcel of their daily discussion. (Sintang et al, 2012) Contributing to discourse on the dialogue of life within the context of its meaning and nature, (Kuruvachira, 2003) stressed that the dialogue of life is the first form of dialogue. He further stressed that it implies concern, respect and hospitality towards the other.…”
Section: Beyond Religious Fanaticism In Nigeria: Perspectives From Th...mentioning
confidence: 99%
“…Dialogue is divided into various forms. Ugwoji, as described by Sintang et al (2012), classifies interreligious dialogue into four kinds, such as "dialogue of life, dialogue of collaboration, dialogue of theological discourse and dialogue of religious experience." Diana Eck as described by Khambali (2015) divided it into six types: "parliamentary dialogue, institutional dialogue, and theological dialogue, dialogue of life, spiritual dialogue and inner dialogue."…”
Section: The Concept Of Interreligious Dialoguementioning
confidence: 99%
“…Diana Eck as described by Khambali (2015) divided it into six types: "parliamentary dialogue, institutional dialogue, and theological dialogue, dialogue of life, spiritual dialogue and inner dialogue." Dialogue of life is described as an interaction between the followers of one religion and another in their daily life (Sintang et al, 2012) while working on a common project like a charity organization in a multi-faith community for a common cause is a dialogue of collaborative work (Majid, 2013).…”
Section: The Concept Of Interreligious Dialoguementioning
confidence: 99%
“…Although Perak seems like a peaceful state, the emergence of conflicts in Perak has a great potential to interrupt national and political stability. Sintang et al (2012) highlighted that inter-religious issues and incidents became more complicated when it deals with the issues of living together and social interaction rather than dealing with the theological issues. Nowadays, there are numerous religious conflict cases especially those related to the place of worship, the right of child custody (Ahmad, Talib, Isa, Gill, Jawan & Mohad, 2014) and the issue of kalimah Allah which can be used by non-Muslim (Nor, 2011).…”
Section: The Background Of Multi-religious Society In Perakmentioning
confidence: 99%
“…Nowadays, there are numerous religious conflict cases especially those related to the place of worship, the right of child custody (Ahmad, Talib, Isa, Gill, Jawan & Mohad, 2014) and the issue of kalimah Allah which can be used by non-Muslim (Nor, 2011). Besides that, other sensitive issues related to religious matters include the use of Quranic and Arabic terminologies, Islamic propagation, funeral process, and the use of halal certificate by non-Muslim businessman (Sintang et al, 2012). Thus, it is clearly showed that religious issues nowadays are no longer dealing with the theological aspect of religion.…”
Section: The Background Of Multi-religious Society In Perakmentioning
confidence: 99%